2019
DOI: 10.1016/j.jhep.2019.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota-driven gut vascular barrier disruption is a prerequisite for non-alcoholic steatohepatitis development

Abstract: During diet-induced dysbiosis the gut vascular barrier is disrupted. Gut vascular barrier disruption is responsible for the translocation of bacteria or bacterial products systemically. Inhibiting gut vascular barrier disruption prevents the development of non-alcoholic steatohepatitis. Obeticholic acid can control gut vascular barrier disruption both in a preventive and therapeutic way.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
397
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 465 publications
(410 citation statements)
references
References 49 publications
7
397
0
6
Order By: Relevance
“…In patients with coeliac disease (CD) with elevated serum transaminases GVB alterations may be responsible for liver damage [59]. Although gut barrier disruption has not been reported to be a pre requisite for nonalcoholic steatohepatitis (NASH) development and belongs to the 'multiple hit' pathogenesis of disease progression [60], more recent observations in preclinical models have shown that disruption of epithelial and vascular barriers in the intestine were early events reported in NASH [61]. Gut-liver axis deterioration has also been described in patients with chronic liver diseases who develop sepsis and multiorgan failure [62,63].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with coeliac disease (CD) with elevated serum transaminases GVB alterations may be responsible for liver damage [59]. Although gut barrier disruption has not been reported to be a pre requisite for nonalcoholic steatohepatitis (NASH) development and belongs to the 'multiple hit' pathogenesis of disease progression [60], more recent observations in preclinical models have shown that disruption of epithelial and vascular barriers in the intestine were early events reported in NASH [61]. Gut-liver axis deterioration has also been described in patients with chronic liver diseases who develop sepsis and multiorgan failure [62,63].…”
Section: Discussionmentioning
confidence: 99%
“…The integrity of this intestinal mucus barrier and the physiological composition of the intestinal microbiome are critical for maintaining homeostasis of the liver-gut axis [111]. Metabolic toxins, especially alcohol abuse or high fat/low fiber diet in NAFLD have been described to disrupt intestinal homeostasis by increasing intestinal permeability and altering microbiota [112,113]. Consequentially, the relative overgrowth of potentially pathogenic bacteria not only drives hepatic inflammatory immune responses and HSC activation due to portal delivery of pathogen-associated molecular patterns (PAMPs, as lipopolysaccharides, peptidoglycans, and flagellin), the altered microbiome also results in intestinal deconjugation of bile acids and therefore production of so-called secondary bile acids that suppress Farnesoid-X Receptor (FXR) signaling [111].…”
Section: Gut Dysbiosismentioning
confidence: 99%
“…FXR is a nuclear receptor activated by bile acids that regulates bile acid, lipid, and glucose metabolism [114,115]. Intestinal FXR signaling physiologically exert protective effects on intestinal epithelial barrier properties [116] and accelerates gut vascular barrier repair [113]. Intestinal accumulation of secondary FXR-suppressing bile acids in chronic liver disease therefore promotes disruption of the intestinal barrier.…”
Section: Gut Dysbiosismentioning
confidence: 99%
“…The GVB, composed of endothelial cells, enteric glial cells and pericytes, prevents intestinal microbes from entering the body circulation [21,22]. Further, Mouries et al demonstrated that high-fat diet (HFD) induced dysbiosis that in turn disrupted GVB and drove the translocation of bacteria or their products into liver [23]. GVB-related research not only helps to understand the interaction between gut microbiota and intestinal barrier but also provides new insights into the prevention of NAFLD by regulation of gut-liver axis.…”
Section: Gut-liver Axismentioning
confidence: 99%